2014
DOI: 10.1590/s0103-84782014000400030
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic factors and genetic group on the selling price formation of beef calves sold in auctions at the Northern region of Paraná State, Brazil

Abstract: The aim of this study is to estimate the effects of phenotypic traits on the fi nal price of calves sold at auctions in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…Our study showed that the higher prices of M calves compared with F were also in agreement with Koetz Junior et al (2014), who demonstrated that M are on average 11.5% more valuable than F calves marketed in the state of Paraná. Similar results were found in auctions studied by Crespo et al (2006) in Uruguay and by Troxel and Barham (2007) end of the analysis period.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Our study showed that the higher prices of M calves compared with F were also in agreement with Koetz Junior et al (2014), who demonstrated that M are on average 11.5% more valuable than F calves marketed in the state of Paraná. Similar results were found in auctions studied by Crespo et al (2006) in Uruguay and by Troxel and Barham (2007) end of the analysis period.…”
Section: Resultssupporting
confidence: 90%
“…In agreement, studies reported that higher valuations are reached using particular genetic groups (Halfman et al, 2009;McHugh et al, 2010;Koetz Junior et al, 2014). However, Barham and Troxel (2007) reported that no specific breed or breed type was marketed for higher prices and the superiority of a given group is dependent on the region where the sale occurred and the future prices for the coming years.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations